Pengaruh Pengalaman Pelanggan Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Pada Minimarket Lawson Jalan Soekarno Hatta Kota Malang - Evellin Okta Vina; Achmad Zaini (CV. ITTC INDONESIA, 2025)
Culinary businesses must develop strategies that ensure customer satisfaction during the consumption of their products and services. However, industry players are only beginning to realize that cultivating customer loyalty is challenging and crucial for achieving business objectives. This research aims to investigate the influence of customer experience and service quality on customer satisfaction among consumers of the Lawson convenience store located on Soekarno Hatta Street, Malang City. The data collection method employed observation and questionnaires. A sample of 100 respondents was selected, comprising Lawson convenience store customers who had made at least one purchase. Data was collected through the distribution of questionnaires and subsequently analyzed using validity tests, reliability tests, classic assumption tests, hypothesis tests, and the coefficient of determination. The research findings indicate that both customer experience and service quality have a positive and significant effect on customer satisfaction. This is evidenced by the multiple linear regression calculation, which yielded a constant value of 2.887. These results demonstrate that customer experience and service quality, both partially and simultaneously, significantly and positively influence customer satisfaction among Lawson convenience store consumers.